Hypothalamic neuronal circuits regulating hunger-induced taste modification - Ou Fu (Nature Portfolio, 2019)
Hunger modulates perception of good and bad tastes. Here, the authors report that orexigenic AgRP neurons in the hypothalamus mediate these effects through glutamatergic lateral hypothalamic neurons that send distinct projections to the lateral septum and lateral habenula.